Antitumorigenic Effect of Tramadol and Synergistic Effect With Doxorubicin in Human Breast Cancer Cells - Huang, Yi-Hsuan; Sue, Sung-How; Wu, Zih-Syuan; Huang, Shih-Ming; Lee, Shih-Yu; Wu, Zhi-Fu (Frontiers in Oncology, 2022)
Background Breast cancer in women is one of the leading causes of cancer mortality worldwide, and curative therapy is the main focus of clinical treatment. Anesthetic-analgesic techniques might alter stress responses and immunity and thereby influence outcomes in cancer patients. This study investigated the effect of tramadol on breast cancer progression and metastasis. Methods The effects of tramadol on two different subtypes of human breast adenocarcinoma cell lines, MDA-MB-231 and MCF-7, were studied with regard to cell growth, migration, colony formation and invasion and normoxic or hypoxic microenvironment for the expression of hypoxia-inducible factor-1α, reactive oxygen species, epithelial-mesenchymal transition related and cyclin-related proteins. The co-administration of tramadol and doxorubicin was studied to determine whether the effective doxorubicin dose might be reduced in combination with tramadol. Results The results showed that tramadol inhibited cell growth at concentrations more than 0.5 and more than 1.0 mg/mL in MDA-MB-231 and MCF-7 cells, respectively. Additionally, cell migration, colony formation and invasion were inhibited in a dose-dependent manner by tramadol in both cell lines. The combination of tramadol and doxorubicin induced synergistic effects in MDA-MD-231 cells and, with specific dosage combinations in MCF-7 cells. Conclusions Tramadol may regulate epithelial-mesenchymal transition and possess cytotoxic effects in breast cancer cells. Tramadol inhibits the progression of breast cancer cells and might be a candidate for combination therapy, especially for triple-negative breast cancer, and is a promising treatment strategy for breast cancer.